The Role of Stratigraphy in Growth Strata Studies: A Case Study from the Middle-Late Cretaceous Deposits in Persian Gulf, SW Iran - Ghaseminia, Fereshteh; Daneshian, Jahanbakhsh; Soleimany, Bahman; Afghah, Massih (International Journal of Geography and Geology, 2016)
The growth strata in the Middle-Late Cretaceous deposits including Kazhdumi, Sarvak and Ilam formations and Lafan Shale in the Well 1 located between Qatar-Iran height and Hormuz Strait in Persian Gulf was studied. The present work is based on the lithostratigraphic analysis and distribution of microfossils. Based on the microfossils content, the age of studied successions is Albian to Campanian. Comparison of seismic points, lithostratigraphic analysis and distribution of microfossils show that growth and generation of anticlines are occurred in the Middle-Late Cretaceous. As of results, the Kazhdumi, Sarvak and Ilam formations and Lafan Shale have potential reservoir and oil trap.